Basic parameters of spontaneous speech as a sensitive method for measuring change during the course of aphasia. - Grande M; Hussmann K; Bay E; Christoph S; Piefke M; Willmes K; Huber W (International Journal of Language & Communication Disorders)
Background: Spontaneous speech of aphasic persons is often scored on rating scales assessing aphasic symptoms. Rating scales have the advantage of an easy and fast scoring system, but might lack sensitivity. Quantitative analysis of either aphasic symptoms or basic parameters provides a useful alternative. Basic parameters are essential units of language like word categories or syntactic completeness and can be identified in both impaired and unimpaired adult and child language. Aims: To examine whether basic parameters of spontaneous speech are more sensitive to change during the course of recovery from aphasia than conventional spontaneous speech rating scales. Methods & Procedures: Spontaneous speech samples of 28 aphasic participants were analysed using a quantitative computer-assisted method as well as conventional spontaneous speech rating scales before and after 7 weeks of intensive language treatment. The analysis focused on the following basic parameters: percentage words, percentage open class words, syntactic completeness, complexity, and mean length of utterances. The participants were also tested with the Aachen Aphasia Test before and after treatment. Outcome & Results: Significant change in at least one basic parameter was observed in 20 participants, while only four participants showed significant change in one of the spontaneous speech rating scales. Conclusions: In comparison with conventional spontaneous speech rating scales, the basic parameters proved to be more sensitive to change. For the time being, however, some limitations remain with regard to the specificity of the basic parameters. Thus, additional data are needed to provide further support of the clinical significance of the measured changes.